Effect of Base Sequence on G-Wire Formation in Solution. (3rd May 2010) - Spindler, Lea; Rigler, Martin; Drevenšek-Olenik, Irena; Ma'ani Hessari, Nason; Webba da Silva, Mateus
Abstract : The formation and dimensions of G-wires by different short G-rich DNA sequences in solution were investigated by dynamic light scattering (DLS) and polyacrilamide gel electrophoresis (PAGE). To explore the basic principles of wire formation, we studied the effects of base sequence, method of preparation, temperature, and oligonucleotide concentration. Both DLS and PAGE show that thermal annealing induces much less macromolecular self-assembly than dialysis. The degree of assembly and consequently length of G-wires (5-6 nm) are well resolved by both methods for DNA sequences with intermediate length, while some discrepancies appear for the shortest and longest sequences. As expected, the longest DNA sequence gives the longest macromolecular aggregates with a length of about 11 nm as estimated by DLS. The quadruplex topologies show no concentration dependence in the investigated DNA concentration range (0.1 mM–0.4 mM) and no structural change upon heating.